Response of microbial communities in the tobacco phyllosphere under the stress of validamycin - Guo, Moyan; Hu, Jingrong; Jiang, Chaoying; Zhang, Yi; Wang, Hancheng; Zhang, Xinghong; Hsiang, Tom; Shi, Caihua; Wang, Qing; Wang, Feng (Frontiers in Microbiology, 2024)
Validamycin, is classified as an environmentally friendly fungicide. It has high efficacy with little associated pollution risk, and it has been used in China on tobacco for many years especially during leaf spot season. To understand changes in microbial communities and functional aspects of the tobacco phyllosphere after exposure to validamycin, the chemical was sprayed on tobacco leaves during brown spot epidemic periods caused by Alternaria alternata, and asymptomatic and symptomatic leaves of tobacco were sampled at different times (0 d before, 5 d, 10 d, and 15 d after application). The fungal and bacterial population diversity and structure were revealed using Illumina NovaSeq PE250 high-throughput sequencing technology, and Biolog-ECO technology which analyzes the metabolic differences between samples by using different carbon sources as the sole energy source. The results showed that the microbial community structure of both asymptomatic and symptomatic tobacco leaves changed after the application of valproate, with the microbial community structure of the asymptomatic tobacco leaves being more strongly affected than that of the symptomatic leaves, and the diversity of bacteria being greater than that of fungi. Phyllosphere fungal diversity in asymptomatic leaves increased significantly after application, and bacterial abundance and diversity in both asymptomatic and symptomatic leaves first increased and then decreased. Validamycin treatment effectively reduced the relative abundance of Alternaria, Cladosporium, Kosakonia, and Sphingomonas in leaves showing symptoms of tobacco brown spot, while the relative abundance of Thanatephorus, Pseudomonas, and Massilia increased significantly after application. Furthermore, the ability to metabolize a variety of carbon sources was significantly reduced in both types of leaves after validamycin application, and both types had a weaker ability to metabolize α-Ketobutyric Acid after application. This study reveals phyllosphere micro-ecological changes in symptomatic and asymptomatic tobacco leaves during different periods after validamycin application and the effects on the metabolic capacity of phyllosphere microorganisms. It can provide some basis for exploring the effect of validamycin on the control of tobacco brown spot.